Syntactic and Semantic features of English of English Verb “Take” in the novels “ The Old Man and The Sea” and “ For Whom The Bell Tools” By Ernest Hemingway with reference to its Vietnamese equivalents / Nguyễn Thị Khánh; NHDKH Assoc.Prof.Dr Lê Văn Thanh - Nguyễn, Thị Khánh
The verb “take” is one of the most commonly used in English. It can be divided into 17 semantic meanings and there are 13 idioms and 37 phrasal verbs containing it. Thus, the verb “take” is rather complicated. The misunderstanding of using the verb “take” causes many problems to English users and translators. The purpose of this study is to investigate the syntactic and semantic features of English verb “take” in the novels “ The Old Man and the Sea” and “ For Whom the Bell Tolls” “ by Ernest Hemingway with reference to their equivalents in theirs translation “ Ông già và biển cả” translated by Lê Huy Bắc and “ Chuông nguyện hồn ai” translated by Nguyễn Vĩnh and Hồ Thể Tần. The study is aimed at three points: (1) pointing out syntactic and semantic features of the verb “take” used in the novel “ The Old Man and the Sea” and “For Whom the Bell Tolls” , (2) finding the similarities and differences between the meanings of the verb “take” in English and Vietnamese translational equivalents, (3) providing some recommendations for the teaching and learning as well as translation of the verb “take” into the target language. This study was designed as a descriptive research with the method of contrastive and componential analysis. According to the data analysis, the result of the study show that the verb “take” coincide in their general meaning. However, the verb “take” in Vietnamese seems to have much more meanings than that in English.